‘Harsh Love’ and Forgiveness - Johnson, James Turner (Studies in Christian ethics, 2015)
While Biggar in chapter 2 of his In Defence of War cites Augustine in support of an argument for forgiveness and reconciliation, this paper argues through a close look at Augustine’s Letters 95 and 139 and Book I of his On Christian Doctrine that Augustine’s view of how the Donatists should be treated focused on their punishment, not on reconciliation in the sense Biggar describes.